Protection strategies for directionally-controlled synthesis of previously inaccessible metal–organic polyhedra (MOPs): the cases of carboxylate- and amino-functionalised Rh(ii)-MOPs. Issue 85 (8th October 2019) - Albalad, Jorge; Carné-Sánchez, Arnau; Grancha, Thais; Hernández-López, Laura; Maspoch, Daniel
Abstract : Herein we report that strategic use of protecting groups in coordination reactions enables directional inhibition that leads to synthesis of metal–organic polyhedra (MOPs) highly functionalized with carboxylic acid and amine groups. Abstract : Herein we report that strategic use of protecting groups in coordination reactions enables directional inhibition that leads to synthesis of highly functionalised metal–organic polyhedra (MOPs), rather than of the extended coordination networks. Using this approach, we functionalised two new porous cuboctahedral Rh(ii )-based MOPs with 24 peripheral carboxylic acid groups or 24 peripheral amino groups.